PENGEMBANGAN APLIKASI KAMUS DAN PENERJEMAH BAHASA INDONESIA – BAHASA BALI MENGGUNAKAN METODE RULE BASED BERBASIS ANDROID - Komang Trya Chandra Resmawan; I Ketut Resika Arthana; I Made Gede Sunarya (Universitas Pendidikan Ganesha, 2015)
This study aimed (1) to design Indonesian translator applications in Balinese language using a rule-based method. (2) to implement a dictionary and translator application design from Indonesian language into Balinese language by using the rule-based method. In its design, the result of translation from Indonesian to the Balinese language is divided into three, namely Bali Alus, Bali Madya, and Bali Kasar.The method used was the research and development using the waterfall model with the requirement definition phase which was the first phase of information gathering and analysis of system requirements, the second phase was the system and software design, it was to draft the application, the third phase was implementation, namely the design implementation phase, and the fourth stage System testing, it was testing the software.The end result of this project was in the form of a dictionary and translator application Indonesian - Balinese language using a rule-based method based on android that can be installed on an android smartphone. Based on the test results, it could be concluded that this application could translate words from Balineseinto Indonesian and vice versa, both basic word, and the word that has been given a prefix or suffix. The translation of Indonesian-Balinese language was producing three types of translation; Bali Alus, Bali Madya, and Bali Kasar.